2011
DOI: 10.1007/s10534-011-9506-6
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of multidimensional gold nanoparticles assisted by Streptomyces hygroscopicus and its electrochemical and antibacterial properties

Abstract: The fabrication of reliable, green chemistry processes for nanomaterial synthesis is an important aspect of nanotechnology. The biosynthesis of single-pot room-temperature reduction of aqueous chloroaurate ions by Streptomyces hygroscopicus cells has been reported to facilitate the development of an industrially viable greener methodology for the synthesis of technologically important gold nanoparticles (AuNPs). Multidimensional AuNPs are generated via the manipulation of key growth parameters, including solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…The AgNPs were mixed into 10 mL of deionized water. Then the biosynthesised AgNPs were freeze-dried, powdered and used for XRD analysis (Sadhasivam et al 2012). EDX measurements of the AgNPs were performed by SEM-EDX (Model Jeol JFSM 6390).…”
Section: Xrd and Edx Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The AgNPs were mixed into 10 mL of deionized water. Then the biosynthesised AgNPs were freeze-dried, powdered and used for XRD analysis (Sadhasivam et al 2012). EDX measurements of the AgNPs were performed by SEM-EDX (Model Jeol JFSM 6390).…”
Section: Xrd and Edx Analysismentioning
confidence: 99%
“…The sharp intense peaks of the spectrum clearly indicated that the particles are in the nanoregime and also crystalline in nature. The size of the crystallite AgNPs was calculated using Debye-Scherrer formula (Sadhasivam et al 2012). The calculated crystallite size of Ag particle is *11.5 nm.…”
Section: Characterisation Of Silver Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis in this approach is on the synthesis and application of the nanoparticles for a maximum societal benefit, with minimal impact on the ecosystem [5]. As both the synthesis and applications of nanoparticles are important, many researchers from both academic and industry are focusing towards biological systems such as plants, marine algae, fungi and bacteria for the production of nanoparticles [6][7][8][9]. The compounds present in the extracts can act as reducing as well as stabilizing agents and render more biocompatibility to biosynthesized nanoparticles [10].…”
Section: Introductionmentioning
confidence: 99%